2023
DOI: 10.3389/fnins.2023.1005096
|View full text |Cite
|
Sign up to set email alerts
|

Early-onset, conjugal, twin-discordant, and clusters of sporadic ALS: Pathway to discovery of etiology via lifetime exposome research

Abstract: The identity and role of environmental factors in the etiology of sporadic amyotrophic lateral sclerosis (sALS) is poorly understood outside of three former high-incidence foci of Western Pacific ALS and a hotspot of sALS in the French Alps. In both instances, there is a strong association with exposure to DNA-damaging (genotoxic) chemicals years or decades prior to clinical onset of motor neuron disease. In light of this recent understanding, we discuss published geographic clusters of ALS, conjugal cases, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 227 publications
0
5
0
Order By: Relevance
“…Amyotrophic lateral sclerosis (ALS) is the most prevalent type of motor neuron disease (MND), a neurodegenerative illness that causes muscle weakness [1]. The incidence of sporadic ALS shows little variation in Western countries, ranging from 1 to 2 per 100,000 person-years [2][3][4][5][6], with an estimated lifetime risk of 1 in 400 [7]. MND is caused by upper motor neuron (UMN) or lower motor neuron (LMN) lesion weakness as shown in Table 1 [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amyotrophic lateral sclerosis (ALS) is the most prevalent type of motor neuron disease (MND), a neurodegenerative illness that causes muscle weakness [1]. The incidence of sporadic ALS shows little variation in Western countries, ranging from 1 to 2 per 100,000 person-years [2][3][4][5][6], with an estimated lifetime risk of 1 in 400 [7]. MND is caused by upper motor neuron (UMN) or lower motor neuron (LMN) lesion weakness as shown in Table 1 [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, ALS has a wide range of survival duration. Most ALS is a sporadic disorder (around 70-80%) and hardly distinguished from a family history case (around 10-20%) [2,[11][12][13][14][15]. The most common familial ALS cases include mutation of the chromosome 9 open reading frame 72 (C9orf72, present in 7.7% of ALS cases), followed by Cu/Zn-superoxide dismutase 1 (SOD1, 2.0%), never in mitosis A (NIMA)related kinase 1 (NEK1, 1.8%), TAR DNA binding protein (TARDBP) (1.4%), and kinesin family member 5A ( KIF5A, 0.8%) [11].…”
Section: Introductionmentioning
confidence: 99%
“…The present finding that gyromitrin-rich false morels were eaten by subjects who subsequently developed ALS raises public health concerns and, in regard to the etiology of sporadic neurodegenerative disease, important questions on the molecular mechanisms that might underpin long-latency, tardive neurotoxicity. While properly focused on environmental exposure to hydrazinic substances—whether in nature or synthetic [ 25 ]—it is also important to understand the role of any genetic susceptibilities, notably acetylation status [ 28 ], which employs the enzyme arylamine N -acetyltransferase 2 (NAT2) to regulate the duration of endogenous exposure to xenobiotics. NAT2 genetic variability determines whether subjects are slow, intermediate or fast acetylators [ 4 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some anecdotal reports have also described unexpected geographic occurrences of ALS [ 37 ]. For instance, conjugal cases have been repeatedly described [ 37 39 ], despite spouses are likely to share many exposures beyond their residency.…”
Section: Discussionmentioning
confidence: 99%
“…Some anecdotal reports have also described unexpected geographic occurrences of ALS [ 37 ]. For instance, conjugal cases have been repeatedly described [ 37 39 ], despite spouses are likely to share many exposures beyond their residency. In 1974, it was reported that three unrelated patients living within one block developed the disease within a short time from each other [ 40 ].…”
Section: Discussionmentioning
confidence: 99%